Substitution and Long-Term Results of the Use of Glass-Ionomeric Cement for Fixation of Artificial Crowns - Gryban, О. М.; Borysenko, Д. А. (Actual Dentistry, 2025)
Relevance. The paper presents data from an experimental electron microscopic study of the fixation of artificial crowns with glass ionomer cements. Subsequently, a clinical study monitored the long-term results of the effectiveness of fixing artificial crowns with glass ionomer cements. Purpose. To experimentally determine the reliability of the attachment of glass ionomer cements to artificial crown materials and the clinical effectiveness of the long-term results of fixing crowns with glass ionomer cements. Material and methods. In the clinical part, studies were conducted on 40 patients with dental crown defects, aged 21–40 years, who underwent fixation of 50 crowns with glass ionomer cement Fuji 1 (GC FUJI 1) and Fuji Plus (Fuji Plus GC). The quality of the adhesive attachment of crowns to hard dental tissues using glass ionomer cement was determined by scanning electron microscopy in the Laboratory of the Molecular Photoelectronics Department of the Institute of Physics, NAS of Ukraine. The study used a scanning electron microscope JSM-100 (JEOL, Japan). Research and conclusions. The data obtained indicate the satisfactory condition of the crowns and marginal periodontium (gums) is maintained. At the long-term observation period of 12 months, 37 (92.5%) patients and 45 (90.0%) fixed crowns were examined. The quantitative value of the Schiller–Pysarev test was on average 0.97 ± 0.07 points, the value of the PMA index was 16.3 ± 0.16%, the RVI index was up to 1.15 ± 0.09 points, and the OHI-S hygiene index was 1.37 ± 0.12 points. Marginal discoloration and manifestations of postoperative sensitivity were not noted. The color of the crowns was not changed. The obtained data indicate that within 12 months after fixation, a satisfactory condition of the crowns and marginal periodontium (gums) is maintained. At the long-term observation period of 24 months, 34 (85.0%) patients and 38 (76.0%) fixed crowns were examined. The quantitative value of the Schiller–Pysarev test was on average 1.03 ± 0.07 points, the value of the PMA index was 18.1 ± 0.16%, the RVI index was up to 1.18 ± 0.09 points, the OHI-S hygiene index was 1.43 ± 0.12 points, which indicates a slight irritation of the marginal periodontium, which the accumulation of dental plaque can explain. The patients were corrected for rational oral hygiene, which decreased the manifestations of gingivitis.